Polymorphisms of the prolactin gene in Iraqi ducks and its association with body weight (Texas Journal of Agriculture and Biological Sciences, 2023)
A study was conducted to explore polymorphism for prolactin gene exon 1. The aim is to investigate how polymorphisms and haplotypes influence the body weight of Iraq ducks. The nucleotide sequence of the PRL gene in ducks was aligned with the GenBank LC565025 sequence using the ClustalW program in Bioedit software, Three polymorphisms (SNP) were observed in Iraq Ducks.(LC565025: g.40 G >T, LC565025 g.41 C >T, LC565025: g.96 A >T, LC565025: g.103 C >A, LC565025: g.168 G >T, LC565025: g.211 G >T, LC565025: g.222 T >A, LC565025Z: g.273 T >C) , And the Haplotype was obtained using the program DNAsp 5.10.And select Four haplotypes, namely haplotype1 (ttaaggtc), haplotype 2 (ttacggtc), haplotype 3 (gcacttac), and haplotype 4 (gctcttac), have been identified in exon 1 of the prolactin gene in Iraqi ducks. According to the presented data, the presence of polymorphism (SNP) and haplotypes of the prolactin gene exon1 did not have a significant effect on the average weights of Iraqi ducks.